2020
DOI: 10.21203/rs.3.rs-48912/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compositional analysis of the bacterial community in colostrum samples from women with gestational diabetes mellitus and obesity

Abstract: Background. Gestational Diabetes Mellitus (GDM) and obesity are threatening health conditions during pregnancy, as they affect the normal function of multiple systems, including neuro-hormonal networks, and adipose, liver, muscle and placenta. GDM and maternal obesity are main triggers to a vicious cycle of metabolic and cardiovascular diseases perpetuated trans-generationally. One of the first stages of this vicious cycle occurs during early lactation as the infant feeds of “disbalanced” breastmilk microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 86 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…It may be a consequence of the observed disruption of the microbiota in these samples. In Mexico, the colostrum from obese mothers overall contains a microbiota with more bacterial species (increased richness) and more diversity between species abundances (decreased evenness) compared to colostrum microbiota from lean mothers [13,14]. Obese colostrum microbiota also include more potentially pathogenic bacteria genus such as Staphylococcus [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be a consequence of the observed disruption of the microbiota in these samples. In Mexico, the colostrum from obese mothers overall contains a microbiota with more bacterial species (increased richness) and more diversity between species abundances (decreased evenness) compared to colostrum microbiota from lean mothers [13,14]. Obese colostrum microbiota also include more potentially pathogenic bacteria genus such as Staphylococcus [14].…”
mentioning
confidence: 99%
“…In Mexico, the colostrum from obese mothers overall contains a microbiota with more bacterial species (increased richness) and more diversity between species abundances (decreased evenness) compared to colostrum microbiota from lean mothers [13,14]. Obese colostrum microbiota also include more potentially pathogenic bacteria genus such as Staphylococcus [14]. This may also partly explain the regulation of immune soluble factors described in obese breastmilk, including decreased TGF-β and sCD14, while IL-1 β, IL-6, IL-8, IL-10, and TNF-α concentrations were not significantly altered [15][16][17].…”
mentioning
confidence: 99%
“…LeMay-Nedjelski et al [ 126 ] found that milk samples obtained from obese mothers with GDM or impaired glucose tolerance contained higher levels of Gemella , compared to normal-weight mothers. Moreover, the colostrum samples of obese mothers with GDM showed higher microbial diversity and increased levels of amino acid and carbohydrate metabolism-related bacteria [ 127 ]. However, the HM microbiota composition reported in these studies was also affected by other confounders, including type of delivery, use of antibiotics, ethnicity and infant sex [ 126 , 127 ].…”
Section: Short- and Long-term Implications Of Hm Microbiota On Maternal And Child Healthmentioning
confidence: 99%
“…Moreover, the colostrum samples of obese mothers with GDM showed higher microbial diversity and increased levels of amino acid and carbohydrate metabolism-related bacteria [ 127 ]. However, the HM microbiota composition reported in these studies was also affected by other confounders, including type of delivery, use of antibiotics, ethnicity and infant sex [ 126 , 127 ]. Consequently, further studies are required to better evaluate potential mechanisms by which HM microbiota from mothers suffering obesity and GDM may influence later health and development.…”
Section: Short- and Long-term Implications Of Hm Microbiota On Maternal And Child Healthmentioning
confidence: 99%
See 1 more Smart Citation